Bio-Liquid Morphological Analysis - S.N. Shatokhina; V.N. Shabalin; M.E. Buzoverya; V.T. Punin (The Scientific World Journal)
Information is presented on the new scientific line in medicine and biology: bio-liquid morphology. The interdisciplinary character of the given research area is emphasized. The problems and prospects of bio-liquid morphological analysis development both in applied and fundamental aspects are discussed.